Music Transformation of Gondrang Sipitu-pitu in Simalungun Community - Nelson, Ricky; Purba, Mauly; Ginting, Pulumun Peterus (Institut Seni Indonesia Yogyakarta, 2025)
This study investigates the transformation and adaptation processes of gondrang sipitu-pitu music within Simalungun society in response to social, cultural, and technological dynamics. Originally serving as a medium for ritual and spiritual communication in the context of Simalungun customs, gondrang sipitu-pitu has undergone significant changes in its musical structure, social function, and performance style due to the influence of religion, modernization, and external cultural forces. The research employs a descriptive qualitative method with a phenomenological approach, drawing upon Margaret Kartomi theory of transformation and adaptation, Jeff Todd Titon theory of musical style, and William F. Ogburn theory of socio-cultural change. The findings reveal that although modern instruments have begun to challenge the dominance of traditional ones, key musical elements such as rhythm, sarunei melodies, and ensemble structure remain preserved. The emerging musical style reflects the creative adaptation of traditional artists to contemporary performance contexts. However, this transformation is also accompanied by critical issues, including the erosion of sacred meaning, the influence of modern aesthetic pressures, and the commodification of local culture. The shift from sacred ritual to popular entertainment raises concerns regarding the authenticity and sustainability of cultural values. Thus, this transformation must be understood not merely as an adaptive process, but as a contested arena of meaning, identity, and cultural power within Simalungun society.